Determining the load for resisted sprint training with sled towing in soccer players. A pilot study - Cánovas, J. F.; Martinez-Valencia, M. A.; Marin-Pagán, C.; Gonzalez-Zaragoza, M.; Alcaraz, P. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sled towing is one of most used training methods to improve specific strength and power during sprinting. Unfortunately, there are no studies about this type of training on soccer players specifically. Two studies (Alcaraz et al., 2009; Lockie et al., 2003), with sprinters and field-sport athletes proposed a regression equation to determine the load for sprint training with sled towing. These equations were based on percentage of athlete`s body mass (Bm). The purpose of this study was to develop an equation that accurately describes the relationship between towing loads and speed in the acceleration phase of sprinting in soccer players. METHODS Fourteen male semi-professional soccer players (23.07 ± 3.29 years; height 1.77 ± 0.07 m; weight 75.43 ± 6.38 kg) were recruited for the study. The tests were performed on a natural grass surface. After a specific warm-up, subjects completed 10 × 20-m sprints, an unloaded sprint and nine ones with different loads according to Bm. Maximum velocity (Vmax) of each sprint was measured with a radar gun with a record data frequency of 33 Hz. The order for the trials was randomized and a five-minute rest period was allocated to remove the effects of fatigue. A regression analysis was used to determine the relationships between load (as a percentage of Bm) and velocity (as a percentage of Vmax over 20-m, established in the unloaded sprint). RESULTS The regression analysis showed the following regression equation: y=-0.995x+101.67, with a value of R²=0.8299. In this equation, "y" represents the percentage of load, and "x" is the required training velocity, as a percentage of Vmax. The R² value reflects a highly significant lineal relationship among these variables (p<0.001). DISCUSSION As expected, an increase in time and a reduction of speed was observed when the load raised. However, the regression equation, behaves differently when compare with other equations published (Alcaraz et al., 2009; Lockie et al., 2003). It seems that a higher slope (m) may reflect a higher level of maximum strength, and therefore, a better performance with high loads. In this study, "m" had a value of -0.995, greater than slope calculated with athletes m = -0.867 (Alcaraz et al., 2009) but less than sport-field athlete`s slope, where m = -1.96 (Lockie et al., 2003). These data may indicate that depending on different variables such as sport modality, strength characteristics, etc. athletes should use a different equation. This study aims to provide a new tool that allows coaches to determine the optimal load for training with soccer players.